(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
In 2007 a research of the macrophytes species composition in three alkalitrophic lakes of Pskov region was conducted with the aim to reveal human impact of experimental activities on Fishery transformation, which were conducted in 1969-1972. The study displayed small changes in higher aquatic plants’ composition: the number of macrophytes species almost haven’t changed, dominant species of emergent vegetation belt maintained their positions, and locations of species listed in the Red Data Book were unchanged. The strong negative impact fishery activities made only on Charophyta stretches, which has disappeared or their areas were much reduced in studied lakes. One of the reasons of small changes is that the lakes belong to macrophyte type, which are more resistant to anthropogenic influences.